Trends of Nomadic Tourism Using Campervan as A Tourism Attraction for Millenials to Travel In Bali - Sari, Retno Juwita; Suarmana, I Wayan Restu (Institut Pariwisata Trisakti, 2022)
Bali has natural beauty from beaches to mountains, which attract tourists to visit, especially the millennial generation. Millennials are said to have a fairly high mobility. The level of their desire to travel is also not small. Therefore this generation is generally known as adventurers. Especially in terms of traveling or taking advantage of free time, this generation has started traveling to new places that are not widely known, and are considered interesting. The rapid development of tourism is currently creating various trends, one of which is nomadic tourism. The term nomadic tourism is still very common among the people. The purpose of this study is to focus on alternative tourism that can be carried out by nomadic tourism for millennials by using a campervan as a tourist attraction for traveling in Bali. The method used is descriptive qualitative. The informant gathering technique used was snowball sampling, in this case the interviewees ranged from tourists using campervans to entrepreneurs providing campervan services. The results of this study are to find out one of the facilities that support nomadic tourism, namely campervans which nomadic travelers have begun to glance at to support their traveling activities around exploring one destination to another. Keywords: The Role of E-Wom, The Intention of The Millenial Generation, Visit Tourism Village